2016
DOI: 10.1016/j.abb.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The preferential heterodimerization of human small heat shock proteins HSPB1 and HSPB6 is dictated by the N-terminal domain

Abstract: Small heat shock proteins are ATP-independent molecular chaperones. Their function is to bind partially unfolded proteins under stress conditions. In vivo, members of this chaperone family are known to preferentially assemble together forming large, polydisperse heterooligomers. The exact molecular mechanisms that drive specific heteroassociation are currently unknown. Here we study the oligomers formed between human HSPB1 and HSPB6.Using small-angle X-ray scattering we could characterize two distinct heterool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 40 publications
5
28
0
Order By: Relevance
“…The equimolar mixture of WT HSPB1 and HSPB6 prepared at 37 o C yielded a broad elution profile on analytical SEC, composed of two peaks with maxima corresponding to a molecular weight of 508 and 160 kDa, in line with previous studies (35). The corresponding eluted fractions contained equimolar amounts of both sHSPs when analysed by SDS-PAGE (Fig.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The equimolar mixture of WT HSPB1 and HSPB6 prepared at 37 o C yielded a broad elution profile on analytical SEC, composed of two peaks with maxima corresponding to a molecular weight of 508 and 160 kDa, in line with previous studies (35). The corresponding eluted fractions contained equimolar amounts of both sHSPs when analysed by SDS-PAGE (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Assuming both sHSPs can freely exchange subunits, random protomer turnover would be expected to result in oligomers containing both homo and heterodimers. Recently, using native mass spectrometry, we have observed that although both sHSPs alone can exchange subunits in such a stochastic fashion, the heterooligomeric complex is composed solely of heterodimers (35). This result, in good agreement with earlier residue specific cross-linking studies (21), supports a heterooligomer model where HSPB1 and HSPB6 preferentially associate at the core dimer level.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, specific interactions of the N-terminal region in intact αBc were inferred by solid-state NMR through chemical shift changes and alterations in dynamics of resonances in the N-terminal region (Mainz et al 2015). Similarly, the N-terminal region of Hsp20 (HspB6) has multiple sites of interaction with a target protein as well as a role in regulating chaperone activity ) whilst also being important in the formation of a hetero-oligomer with Hsp27 (Heirbaut et al 2016). There is evidence from interactome studies that the Nterminal region of plant sHsps is involved in interacting with amorphously aggregating target proteins (Jaya et al 2009).…”
Section: Introductionmentioning
confidence: 99%